2012
DOI: 10.1037/a0026262
|View full text |Cite
|
Sign up to set email alerts
|

The youth form of the Motivators of and Barriers to Health-Smart Behaviors Inventory.

Abstract: The MB-HSBI-Youth may be a useful and novel tool for developing assessment-based, culturally sensitive health promotion programs customized to be responsive to the motivators of and barriers to health-smart behaviors identified in target communities, particularly those communities whose members are mostly racial/ethnic minorities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…11 For example, it has been found that early adolescent dietary intake patterns may help predict obesity in young adulthood in women. 12,13 It has also been found that adolescents who participate in physical education 5 days a week may decrease the odds of adult obesity by 28%.…”
Section: Motivators Of and Barriers To Eating Foods And Snacks Among mentioning
confidence: 99%
See 1 more Smart Citation
“…11 For example, it has been found that early adolescent dietary intake patterns may help predict obesity in young adulthood in women. 12,13 It has also been found that adolescents who participate in physical education 5 days a week may decrease the odds of adult obesity by 28%.…”
Section: Motivators Of and Barriers To Eating Foods And Snacks Among mentioning
confidence: 99%
“…), 2 multivariate analyses of variance (MANOVAs) were used given the conceptual inverse associations of motivator scales and barrier scales and of the subscales within each scale. Prior to conducting these MANOVAs, age was dichotomized to reflect the ages of adolescents in middle school (ie, ages [11][12][13][14] and the ages of adolescents in high school (ie, ages [15][16][17]. Additionally, assumptions necessitated by a MANOVA were examined.…”
Section: Multivariate Analyses Of Variancementioning
confidence: 99%
“…However, there are some areas of consideration to be noted. Some of the articles in which measures were piloted (Tucker et al, 2012;DeVet et al, 2014) described explicit efforts to ensure that the development and validation of their measure involved a process and/or sample that was culturally, ethnically, racially, and/or socioeconomically diverse. Notwithstanding these exceptions, the majority of studies were originally validated in homogenous samples and are reflective of an ever-present and longstanding need to diversify participants in psychological research (Graham, 1992 Affective and/or emotional influences may play an important role in eating behaviors for some groups more than others; for example, one study suggested that among those receiving inpatient treatment for eating disorders 94% also experienced mood disorders, and 56% experienced anxiety disorders (Blinder, Cumella, & Sanathara, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Instruments to assess sociocultural factors, such as the 2F or the MB-HSBI-Youth, have numerous applications in practice and research (Georgiou, 2005;Tucker et al, 2012). Namely, these tools are helpful in understanding the social and environmental factors that influence adolescents' self-determination to regulate eating behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation